Level of heavy metals in sliced watermelon fruits in selected markets in Akure, Nigeria - Oladele, Oluwole Olakunle (2021)
The nickel (Ni) levels detected in the sliced fruits across the markets ranged from 0.20 ± 0.01 (Isinkan) to 1.42 ± 0.02 mg kg−1 (Oja-Oba), while chromium (Cr) levels detected ranged from 0.04 ± 0.01 (Shasha) to 0.12 ± 0.02 mg kg−1 (Oja-Oba). Copper (Cu) levels ranged from 0.04 ± 0.00 (Isinkan) to 0.13 ± 0.03 mg kg−1 (Oja-Oba). Remarkably, cadmium and lead were not detected in any of the sliced fruits. Additionally, the levels of Cu in this study were generally below the WHO permissible levels. However, the levels of Ni in all the sliced watermelon fruits, aside the one purchased from vendor D in Isinkan market, were found to be above the permissible levels. Similarly, Cr levels in the sliced fruits purchased only from vendors A, E, and F in Shasha and vendor C in Oja-Oba markets were also found to be above the permissible levels.